The Use of Lumio Applications in the Maharah Qiraah and Chitabah in Learning Arabic - Imas Maisarah; Anisul Imamah (Amandemen: Journal of Learning, Teaching and Educational Studies, 2024)
This research discusses how the use of learning media makes it easier for teachers and students to understand the material and improves the increasingly rapid technological advances. In this research the technology used is the Lumio application. The Covid-19 outbreak has caused the need for technology in the world of education to increase because learning is no longer carried out offline but online. Therefore, the learning media used must also be updated to support effective learning. Apart from that, the Lumio application was chosen because of its conditional nature, it can be used offline or online. The method used in this research is a qualitative descriptive method using observation and interview techniques. Based on the analysis carried out, it was found that in learning Arabic, Lumio is very supportive so that it can be used in all four directions. Using this platform is also very easy to learn and apply. Lumio also has many features that can be used and utilized in learning.